(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This study was conducted in the agricultural research station- College of Agriculture and Marshlands, University of Thi Qar, Iraq. The paper presents the effect of spraying nano-iron and Ascorbic acid on some of the vegetative characteristics, chemical components and oil of the mint plant (Mentha pipreta L.), with three variants (0 control, 30 and 60) mg/l as nano-Iron source were tested, and three variants (0 control, 50 and 60) mg/l as Ascorbic acid source were tested. Results shown that the plants treated at a concentration of 60 mg/l with nano -iron fertilizer and Ascorbic acid were superior in plant height (28.11, 25.96) cm; leaves number (73.59,69.24)leaf/plant; branches number(16.90, 14.28)branch/plant; chlorophyll content in leaves (11.85, 10.77)mg/100 mg; total soluble carbohydrates (1.873, 1.563)mg/g; percentage of volatile oil in the leaves(0.6794, 0.6083 )%; amount of volatile oil per plant (0.286, 0.309)g. respectively.